The declining accounting profession: unravelling the causes and implications for the future - Mohamad Din, Nornadzifah; Abdullah @ Abd Aziz, Azilawati (Faculty of Accountancy, Universiti Teknologi MARA (UiTM) Cawangan Kelantan, 2025)
The accounting profession has historically been regarded as a prestigious and indispensable career, essential to both the public and private sectors. Accountants play a crucial role in financial evaluation, forecasting, and ensuring compliance with policies and standards, thereby maintaining financial integrity and corporate accountability. However, recent trends indicate a significant decline in the number of individuals pursuing and remaining in accounting careers. Reports highlight a 17% reduction in accountants and auditors, with over 300,000 professionals leaving the industry since 2019. This trend is exacerbated by the retirement of experienced professionals and a decreasing number of new entrants into the field. Furthermore, statistics reveal a sharp decline in accounting degree completions and CPA exam applicants, raising concerns about the profession's sustainability. Contributing factors to this decline include work-life balance challenges, limited interest among fresh graduates, and apprehensions regarding technological advancements potentially replacing traditional accounting roles. The diminishing workforce in accounting not only places additional burdens on existing professionals but also raises concerns about the long-term viability and integrity of financial reporting. This paper aims to explore and examine the key factors influencing the decline in the accounting profession and their broader implications for the industry.